The effect of social context and social scale on the perception of relationships in monk parakeets. Issue 1 (1st February 2015) - Hobson, Elizabeth A.; John, Darlene J.; Mcintosh, Tiffany L.; Avery, Michael L.; Wright, Timothy F.
Abstract: Social relationships formed within a network of interacting group members can have a profound impact on an individual's behavior and fitness. However, we have little understanding of how individuals perceive their relationships and how this perception relates to our external measures of interactions. We investigated the perception of affiliative and agonistic relationships at both the dyadic and emergent social levels in two captive groups of monk parakeets ( Myiopsitta monachus, n = 21 and 19) using social network analysis and playback experiments. At the dyadic social scale, individuals directed less aggression towards their strong affiliative partners and more aggression towards non-partner neighbors.At the emergent social scale, there was no association between relationships in different social contexts and an individual's dominance rank did not correlate with its popularity rank. Playback response patterns were mainly driven by relationships in affiliative social contexts at the dyadic scale. In both groups, individual responses to playback experiments were significantly affected by strong affiliative relationships at the dyadic social scale, albeit in different directions in the two groups. Response patterns were also affected by affiliative relationships at the emergent social scale, but only in one of the two groups. Within affiliative relationships, those at the dyadic social scale were perceived by individuals in both groups, but those at the emergent social scale only affected responses in one group. These results provide preliminary evidence that relationships in affiliative social contexts may be perceived as more important than agonistic relationships in captive monk parakeet groups. Our approach could be used in a wide range of social species and comparative analyses could provide important insight into how individuals perceive relationships across social contexts and social scales.